2003
DOI: 10.1016/s1352-2310(02)01007-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for chlorine-enhanced urban ozone formation in Houston, Texas

Abstract: Urban air pollution is characterized by high ozone levels, formed when volatile organic compounds (VOCs) are oxidized in the presence of nitrogen oxides (NO x ). VOC and NO x emissions controls have traditionally been implemented to reduce urban ozone formation, however, a separate chemical species implicated in ozone formation in Houston, TX and possibly other urban areas is the chlorine radical (Cl Á ). Cl Á enhances tropospheric VOC oxidation, but is not included in models used to develop air quality attain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 12 publications
4
95
0
Order By: Relevance
“…Outside of the MBL and polar regions, natural emissions of reactive halogen species have been observed in volcano plumes (Bobrowski et al, 2007) and over salt lakes (Kamilli et al, 2016;Stutz, 2002). Anthropogenic sources include industrial emissions (Chang and Allen, 2006;Riedel et al, 2013;Tanaka et al, 2003), oil and gas production , water treatment (Chang et al, 2001), biomass burning (Lobert et al, 1999), engine exhaust (Osthoff et al, 2008;Parrish et al, 2009), and NO x -mediated heterogenous reactions, notably the production of ClNO 2 via reactive uptake of N 2 O 5 onto particles containing Cl − (Thornton et al, 2010). Recent studies have found that models underpredict the abundance of reactive halogen species, suggesting incomplete understanding of their sources (Faxon and Allen, 2013;Faxon et al, 2015;Simpson et al, 2015;Thornton et al, 2010).…”
Section: S Wang and L Hildebrandt Ruiz: Secondary Organic Aerosomentioning
confidence: 99%
See 3 more Smart Citations
“…Outside of the MBL and polar regions, natural emissions of reactive halogen species have been observed in volcano plumes (Bobrowski et al, 2007) and over salt lakes (Kamilli et al, 2016;Stutz, 2002). Anthropogenic sources include industrial emissions (Chang and Allen, 2006;Riedel et al, 2013;Tanaka et al, 2003), oil and gas production , water treatment (Chang et al, 2001), biomass burning (Lobert et al, 1999), engine exhaust (Osthoff et al, 2008;Parrish et al, 2009), and NO x -mediated heterogenous reactions, notably the production of ClNO 2 via reactive uptake of N 2 O 5 onto particles containing Cl − (Thornton et al, 2010). Recent studies have found that models underpredict the abundance of reactive halogen species, suggesting incomplete understanding of their sources (Faxon and Allen, 2013;Faxon et al, 2015;Simpson et al, 2015;Thornton et al, 2010).…”
Section: S Wang and L Hildebrandt Ruiz: Secondary Organic Aerosomentioning
confidence: 99%
“…Studies have shown that chlorine-initiated oxidation of α-pinene (Cai and Griffin, 2006;Ofner et al, 2013), toluene (Cai et al, 2008;Huang et al, 2014;Karlsson et al, 2001), and polycyclic aromatic hydrocarbons (PAHs; Riva et al, 2015) leads to SOA formation, with SOA yields close to unity reported for select PAHs . Reactive chlorine species could also enhance OH-radical propagation , nocturnal NO x recycling (Riedel et al, 2012;Thornton et al, 2010), and ozone production (Tanaka et al, 2003), further increasing the oxidative capacity of the atmosphere.…”
Section: S Wang and L Hildebrandt Ruiz: Secondary Organic Aerosomentioning
confidence: 99%
See 2 more Smart Citations
“…The gas phase reaction with ozone is too slow at ozone mole fractions observed at Cape Point even at the highest rate constant reported (Lin et al, 2006), and the reactions with OH and H 2 O 2 are too slow at their concentrations expected in the MBL. But the vegetation of the Cape Peninsula might emit volatile organic compounds that in combination with marine chlorine emissions might enhance the reactivity without O 3 destruction (Chang et al, 2002;Tanaka et al, 2003) and reduce the lifetime of elemental mercury. But this explanation does not fit the observations by Temme et al (2003) and neither those of Joachim Kuss (unpublished results), the latter with DEs far from any vegetated coast.…”
Section: Conclusion and Summarymentioning
confidence: 99%